2019
DOI: 10.9734/jemt/2019/v23i430136
|View full text |Cite
|
Sign up to set email alerts
|

An Estimation of Working Capital Management on Profit Using Logistic Regression and Discriminant Analysis

Abstract: Aims: This paper estimates working capital management on profit using logistic regression and discriminant analysis on manufacturing and industrial firms in Ghana. Study Design: Research Paper. Place and Duration of Study: Ghana, Secondary data for 2009 to 2014. Methodology: Data in the form of ratios were computed from the audited annual financial reports of 13 manufacturing and industrial firms listed on the Ghana Stock Exchange covering the period from 2009 to 2014.The ratios were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In addition, managers should consider implementing aggressive WC policies to enhance profitability. Darkwah et al (2019) explored the impact of WCM on profit deploying logistic regression (LR) and discriminant analysis (DA) on thirteen listed firms operating in the industrial/manufacturing sectors of Ghana, utilizing financial data from final accounts, spanning 2009 to 2014. Findings indicated that the LR of the prognostic variable i.e., Profit on the journal.ump.edu.my/ijim ◄ explanatory variables were statistically significant and that, there was no difference in variances for two firm categorizations.…”
Section: Empirical Literaturementioning
confidence: 99%
“…In addition, managers should consider implementing aggressive WC policies to enhance profitability. Darkwah et al (2019) explored the impact of WCM on profit deploying logistic regression (LR) and discriminant analysis (DA) on thirteen listed firms operating in the industrial/manufacturing sectors of Ghana, utilizing financial data from final accounts, spanning 2009 to 2014. Findings indicated that the LR of the prognostic variable i.e., Profit on the journal.ump.edu.my/ijim ◄ explanatory variables were statistically significant and that, there was no difference in variances for two firm categorizations.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Working capital management is predicated on the ratio of liquidity. It entails controlling and planning current assets and current liabilities in a manner that, on the one hand, eliminates the risk of failure due to short-term obligations and, on the other, prevents high investment in these assets (Darkwah, Nortey, Asare-Kumi & Asare, 2019). This is because there are current assets and current liabilities.…”
Section: Introductionmentioning
confidence: 99%